2005
DOI: 10.1007/11560548_13
|View full text |Cite
|
Sign up to set email alerts
|

Saturation-Based Symbolic Reachability Analysis Using Conjunctive and Disjunctive Partitioning

Abstract: Abstract. We propose a new saturation-based symbolic state-space generation algorithm for finite discrete-state systems. Based on the structure of the high-level model specification, we first disjunctively partition the transition relation of the system, then conjunctively partition each disjunct. Our new encoding recognizes identity transformations of state variables and exploits event locality, enabling us to apply a recursive fixed-point image computation strategy completely different from the standard brea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
36
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 34 publications
(36 citation statements)
references
References 26 publications
0
36
0
Order By: Relevance
“…When this happens, the Kronecker encoding of event e has R (k) e = I n k , while the quasi-reduced or the fully-reduced forms alone cannot take advantage of these common patterns. To exploit these patterns, a combination of the fully-reduced form, for unprimed level X k , and a new identity-reduced form (Ciardo & Yu, 2005) for primed level X k , is needed. This allows us to encode R e in an EV * MDD which has nodes only at (unprimed and primed) levels corresponding to state variables in S e .…”
Section: Adopting Ideas From Kronecker Encodings: Identity Patternsmentioning
confidence: 99%
See 1 more Smart Citation
“…When this happens, the Kronecker encoding of event e has R (k) e = I n k , while the quasi-reduced or the fully-reduced forms alone cannot take advantage of these common patterns. To exploit these patterns, a combination of the fully-reduced form, for unprimed level X k , and a new identity-reduced form (Ciardo & Yu, 2005) for primed level X k , is needed. This allows us to encode R e in an EV * MDD which has nodes only at (unprimed and primed) levels corresponding to state variables in S e .…”
Section: Adopting Ideas From Kronecker Encodings: Identity Patternsmentioning
confidence: 99%
“…This idea was first introduced for logic analysis (Ciardo & Yu, 2005) but it is also related to Equation 76, which expresses R as a sum of products. This is particularly appropriate for globally-asynchronous locally-synchronous systems, where not only each state change is due to an (asynchronous) event e ∈ E, but the occurrence of e de-pends on and (synchronously) changes only a few state variables.…”
Section: Beyond Kronecker: Disjunctive-then-conjunctive Partition Encmentioning
confidence: 99%
“…In several studies, Saturation has been shown superior to BFS-style iterations when symbolically computing least fixpoints for asynchronous models [8,9,10]. The challenge in adapting Saturation to bounded model checking lies in the need to bound the symbolic traversal in the nested fixpoint computations.…”
Section: Bounded Reachability Checking Using Decision Diagramsmentioning
confidence: 99%
“…A version of Saturation using ADDs can be obtained by extending the MDD-based Saturation algorithm of [10], so that it uses an ADD to store the states and their distances, instead of a simple MDD. The ADD has B + 1 terminal nodes corresponding to the distances of interest, {0, 1, .…”
Section: Bounded Reachability Checking Using Decision Diagramsmentioning
confidence: 99%
See 1 more Smart Citation